THE EFFECT OF SOCIAL COMPARISON ON FEMALE MODELS BODY IMAGE - Maria Jane Tienoviani Simanjuntak; Juli Sarah Harahap (Biopsikososial: Jurnal Ilmiah Psikologi Fakultas Psikologi Universitas Mercubuana Jakarta, 2022)
Being female models are identical to have an attractive physical appearance such as a tall, thin and clean white skin, which this makes the models focus on their physical appearance. Furthermore, models have a tendency to compare themselves with others in order to fulfill the demands of the modeling industry. This study aims to determine whether there is an effect of social comparison on body image in the female model. The sample of this research is 275 female models with an age range of 18-30 years who are in Jakarta and are members of a modeling agency. Data were collected using social comparison and body image measurement tools. Social comparison was measured using Physical Appearance Comparison Scale-Revised (PACS-R) and body image measured using the Multidimensional Body-Self Relations Questionnaire–Appearance Scales (MBSRQ–AS). The results of this study prove that social comparison has a significant effect on the body image of female models in Jakarta. The effective contribution of social comparison to body image is 46.3%. The Implications of the research could be the baseline for women's empowerment institutions in increasing knowledge for women so that they are able to accept their physical appearance as it is. Specifically, this research is actually a reflection for all model agencies in terms of represent beauty to people through products or brand.